Focusing on Hippo Pathway in Stem Cells of Oral Origin, Enamel Formation and Periodontium Regeneration. (31st December 2022) - Wang, Tianyi; Li, Kehan; Liu, Hanghang; Luo, En
ABSTRACT: Hippo pathway is a cellular regulatory pathway composed of core molecules such as MST1/2, LATS1/2, SAV1, MOB1A/B and downstream YAP/TAZ. Fully involved in regulating cell proliferation, differentiation, migration and apoptosis, the Hippo pathway is critical in regulating stem cells of oral origin, for instance, DPSCs and PDLSCs, enamel formation and periodontium regeneration. Here, we summarized the Hippo pathway involved in these progresses and concluded crosstalks of the Hippo pathway with BCL-2, ERK1/2, ROCK, TGF-β/BMP and Wnt/β-catenin pathways, hoping to provide foundation for further clinical therapy.